Targeting UGT2B15 and NR1H4 interaction: a novel therapeutic strategy for polycystic ovary syndrome using naftopidil enantiomers - Xiufen Zheng; Zikai Chen; Miao Liang; Liting Zhou; Miaoru Wang; Silin Zhang; Shuyun Zhang; Lei Ma; Wei Yi; Xiawen Liu (Journal of Ovarian Research, 2025)
Abstract Background Polycystic ovary syndrome (PCOS) is a prevalent endocrine disorder among women of reproductive age. It is characterized by hyperandrogenism, ovulatory dysfunction, and the presence of polycystic ovarian morphology (PCOM) on ultrasound, often accompanied by metabolic disturbances such as insulin resistance and obesity. Current treatments, including oral contraceptives and anti-androgen medications, often yield limited efficacy and undesirable side effects. This study investigates the role of UGT2B15, an essential enzyme for androgen metabolism, in PCOS pathogenesis and its potential as a therapeutic target. Methods We used RNA sequencing to examine the effects of UGT2B15 knockdown in KGN cells. To modulate UGT2B15 expression, we employed siRNA and (R)/(S)-NAF (naftopidil), a chemical inducer of UGT2B15 identified in our previous studies on a prostate hyperplasia model. The effects of siRNA and (R)/(S)-NAF on dihydrotestosterone (DHT) levels, cell apoptosis, and the expression of apoptosis-related proteins in KGN cells were evaluated. In a PCOS mouse model, we assessed the effects of (R)-NAF and (S)-NAF on serum androgen levels, menstrual cycles, ovarian morphology, and UGT2Bs expression. Additionally, luciferase reporter and ChIP assays were utilized to study UGT2B15 regulation by NR1H4. Results Elevated androgens were found to suppress UGT2B15 expression in ovarian granulosa cells, leading to DHT accumulation and apoptosis. (R)-NAF and (S)-NAF treatments reversed these effects, alleviating PCOS symptoms in mice such as hyperandrogenism, irregular menstrual cycles, and the presence of ovarian cysts. NR1H4 negatively regulated the transcription of UGT2B15 in KGN cells. (R)-NAF and (S)-NAF disrupted NR1H4 binding to the UGT2B15 promoter without affecting its protein levels, indicating direct interference with its regulation. Conclusions UGT2B15 represents a promising target for novel PCOS therapies by modulating androgen metabolism and protecting ovarian granulosa cells from apoptosis. (R)-NAF and (S)-NAF regulate UGT2B15 by disrupting NR1H4's binding to its promoter, implying potential therapeutic compounds for PCOS treatment.